PENGARUH POLA KERJA DAN KECERDASAN EMOSIONAL TERHADAP BUDAYA ORGANISASI KARYAWAN (STUDI KASUS PADA STIKOM CKI JAKARTA) - Atik Budi Paryanti (JURNAL MITRA MANAJEMEN, 2013)
ABSTRACTAtik Budi Paryanti, Suryadarma University, November 2013, Influence Pattern Against EmotionalIntelligence Work and Organizational Culture, (Case study In STIKOM CKI Jakarta).The purpose of this study was to determine the influence of work pattern and emotional intelligence onorganization culture at STIKOM CKI JAKARTA. The influence of emotional intelligence as an element of humanresources within an organization need to be reviewed and developed. Good working attitude needed to improveorganizational performance. A very significant in improving the performance of the organization to face thechallenges of global competition is through work pattern and emotional intelligence, the end goal is to makecontinuous improvements in order to focus on customer pattern. With the above background, the researcher isinterested in doing research on human resources in STIKOM CKI JAKARTA, it is known that the organization hasimplemented government management standards. There are three variables studied influence, namely: 1) workpattern (X1), 2) emotional intelligence (X2), to 3) the organization culture (Y).The method used in this study is a survey method with causal approach. Meanwhile, to analyze data aboutwhether or not the effect of one variable with another variable using path analysis (path analysis). Samplecollection technique is to use the technique of "probability sampling", ie the "simple random sampling", obtained40 samples from all populations were available. Validity and reliability data for each variable using the MicrosoftExcel software, then performed the normality test, homogeneity and linearity test that analyzes the requirementsare met. The hypothesis was tested with SPSS Statistics software covering correlation test and regression test,so it can perform comparison t test and F test on all variables studied.From the analysis of X1 on Y obtained path coefficient (ρyx1) = 0.715 with t = 13.805 and the real level α = 0.05 isobtained t table = 1.6849. Since the value of t count > t table, then reject Ho, hence path coefficient is significant,it is evident that a positive work pattern directly influences the organization culture. X2 analysis of the Y valuesobtained path coefficients (ρyx2) = 0.621 at t = 3.738 and the real level α = 0.05 is obtained t table = 1.6849. Sincethe value of t count > t table, then reject Ho is thus very significant path coefficients, it is evident that theemotional intelligence in a positive direct influence on organization culture. Analysis of X1 and X2 on Y obtainedcoefficient of determination (rx1x2) = 0.933 with F = 184.361 count and the real level α = 0.05 and obtained F table= 3.23. Since the value of F count > F table, then reject Ho is thus very significant path coefficients, it is evidentthat the work pattern and culture in a positive direct influence on organization culture.Keywords: influence, work pattern, emotional intelligence, organization culture